The Relevance of Endometrioid Cysts in Gynecology - Temirova Dilnoza Olimjonovna (American Journal of Bioscience and Clinical Integrity, 2025)
Endometriosis, particularly in the form of endometrioid cysts, remains one of the most pressing issues in contemporary gynecology. Despite its prevalence, gaps remain in understanding its etiology and pathogenesis, and no single treatment guarantees a cure. This study aims to investigate current diagnostic and therapeutic strategies for endometrioid cysts, highlighting the role of laparoscopic intervention and hormonal therapy. Through a clinical-analytical approach, the study evaluates patients with confirmed endometrioid ovarian cysts, analyzing the outcomes of surgical and pharmacological treatments. Findings show that while surgery—especially cystectomy—is effective in pain relief and improving fertility potential, recurrence is common without proper anti-relapse hormonal support. Comparative analysis suggests that continuous combined oral contraceptives (COCs) offer significant preventive value. The implications point to a need for individualized management strategies based on patient reproductive goals, symptom severity, and cyst characteristics. Further research is required to refine diagnostic tools and explore long-term therapeutic combinations to reduce recurrence and improve patient quality of life..